Pengaruh Kualitas Pelayanan Check In Counter Terhadap Kepuasan Penumpang Maskapai Lion Air Di Bandar Udara Internasional Jenderal Ahmad Yani Semarang - Lindiyani; Hodi (CV. Aksara Global Akademia, 2023)
Air transportation is people's main choice for traveling long distances in a short time so that it is more effective and efficient both for business purposes and urgent needs. Air transportation users make companies work extra to improve the quality of service to customers who are satisfied with the services that have been provided. Companies must be able to continue to read or find out what customers need to achieve the maximum possible level of customer satisfaction. The importance of customer satisfaction can provide benefits, including closer and harmonious company and customer relationships. The existence of this study aims to determine the effect of service quality Check-in Counter on Lion Air airline satisfaction at Jenderal Ahmad Yani Airport, Semarang. This study uses a quantitative research method, where the population used is the number of Lion Air passengers for 2 months and the sample taken is 100 passengers. The sampling technique in this study was to use a purposive sampling technique. research instrument using a type of Likert scale. The results showed that the quality of check-in counter service had an effect on passenger satisfaction. This is evidenced by the results of the t test where the t_hitung is 14.879 > t_tabel 1.660 with a significant value of 0.000 < 0.05. For the coefficient of determination (R2) 69.3% the satisfaction variable can be explained by the service quality variable with a difference (100-69.3%) 30.7% influenced or explained by other variables not included in the study.